Do the Cost Stickiness in The Selling, General and Administrative Costs Occur in Manufacturing Companies in Indonesia? - Paskah Ika Nugroho; Wulan Endarti (The Indonesian Journal of Accounting Research, 2014)
Abstract: The purpose of this research is to determine whether the cost stickiness occurred in manufacturing companies in Indonesia. Cost stickiness of the cost increase can be seen from the higher cost of a rise in the volume of activity when compared with the cost decline as volume decreased activity. This study uses two models with the logarithm of the change of variable selling, general and administrative costs (SG&A) costs as the dependent variable during the logarithmic change in operating income, a dummy variable intensity increase of income and assets as an independent variable. Research samples using 135 manufacturing companies in the period 2009- 2011. This study could not find any cost stickiness in manufacturing companies in Indonesia. However, we found that the higher the intensity of the assets of the company, the higher cost stickiness.Abstrak: Tujuan penelitian ini adalah untuk mengetahui apakah perilaku biaya terjadi pada perusahaan manufaktur di Indonesia. Cost Stickinessdari peningkatan biaya dapat dilihat dari biaya yang lebih tinggi dari peningkatan volume aktivitas jika dibandingkan dengan penurunan biaya karena volume kegiatan menurun. Penelitian ini menggunakan dua model dengan logaritma perubahan biaya variabel penjualan, biaya umum dan administrasi (SG & A) sebagai variabel dependen sedangkan perubahan logaritmik dalam pendapatan operasi, peningkatan intensitas variabel dummy pendapatan dan aset sebagai variabel independen. Sampel penelitian menggunakan 135 perusahaan manufaktur pada periode 2009- 2011. Studi ini tidak menemukan kekakuan biaya di perusahaan manufaktur di Indonesia. Namun, kami menemukan bahwa semakin tinggi intensitas aset perusahaan, semakin tinggi pula Cost Stickiness-nya.